FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI MODERASI - Alfasani, Rismada; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis study is aimed to examine the influence of competence, independence and professional expertise to the auditquality with the auditor ethics as the moderating variable. The population is all auditors who have been workingat Public Accountant Firm in Surabaya. This research has been done by using three kinds of research variables,i.e. dependent variable, independent variable, and moderating variable. The dependent variable i.e. audit quality;independent variables are competence, independence and professional expertise, and moderating variables i.e.auditor ethics. The samples are auditors who have been working at Public Accountant Firm in Surabaya. Thedata is the primary data which has been collected by issuing questionnaires to the respondents. The analysismethod has been done by using moderating regression analysis. The result of the research shows that auditorethics give positive correlation in moderating the correlation of competence, independence and professionalexpertise to the audit quality, it means that auditor ethics can strengthen the correlation whereas the t testshows that the result of competence, independence, professional skills and auditor ethics give significantinfluence to audit quality.Keywords: Competency, independency, professional skill, auditor ethic, audit quality.